2003
DOI: 10.1088/1126-6708/2003/10/064
|View full text |Cite
|
Sign up to set email alerts
|

Holography and hydrodynamics: diffusion on stretched horizons

Abstract: We show that long-time, long-distance fluctuations of plane-symmetric horizons exhibit universal hydrodynamic behavior. By considering classical fluctuations around black-brane backgrounds, we find both diffusive and shear modes. The diffusion constant and the shear viscosity are given by simple formulas, in terms of metric components. For a given metric, the answers can be interpreted as corresponding kinetic coefficients in the holographically dual theory. For the near-extremal Dp, M2 and M5 branes, the comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

82
1,092
3
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 690 publications
(1,189 citation statements)
references
References 29 publications
82
1,092
3
2
Order By: Relevance
“…P = ε/3 and ζ = 0 follow just from conformal invariance. 4πη/s = 1 for the fluid in any non-Abelian gauge theory with a dual gravitational description, in the strong coupling and large-N c limit [34][35][36][37]. Note that the stress-energy tensor depends on symmetric combinations of the fluid gradients ∂ α u β and is independent of the fluid vorticityω…”
Section: Gravitational Description Of a Moving Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…P = ε/3 and ζ = 0 follow just from conformal invariance. 4πη/s = 1 for the fluid in any non-Abelian gauge theory with a dual gravitational description, in the strong coupling and large-N c limit [34][35][36][37]. Note that the stress-energy tensor depends on symmetric combinations of the fluid gradients ∂ α u β and is independent of the fluid vorticityω…”
Section: Gravitational Description Of a Moving Fluidmentioning
confidence: 99%
“…By rearranging terms we have found a more compact version of this expression: 35) JHEP02 (2014)068 where U µ ≡ u µ +sw µ denotes the component of fluid 4−velocity u µ that is perpendicular to the heavy quark 4−velocity w µ . This (deceptively) compact expression for the drag force arising due to fluid gradients at first order is the main result of this paper.…”
Section: Jhep02(2014)068mentioning
confidence: 99%
“…See [52] for case (iii). A quite general formula for the ratio of shear viscosity to entropy density was first derived in [53] and reproduced by different methods in [54].…”
Section: Gauge/gravity Correspondencementioning
confidence: 99%
“…In a series of papers [9,26,28,29,31,32,34,35] an identification of hydrodynamic modes with gravity objects was achieved leading to a detailed gravity description of the hydrodynamics in a strongly coupled fluid. Recently this framework has been extended to second order hydrodynamics [93,94,95,96].…”
Section: More Phenomenology From Ads/cftmentioning
confidence: 99%
“…We also restate the neccessary assumptions and put down the most important formulae. A detailed derivation can be found in [31] while a review of the complete subject may be found in [9].…”
Section: Membrane Paradigmmentioning
confidence: 99%